2019
DOI: 10.1038/s12276-019-0286-3
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix, regional heterogeneity of the aorta, and aortic aneurysm

Abstract: Aortic aneurysm is an asymptomatic disease with dire outcomes if undiagnosed. Aortic aneurysm rupture is a significant cause of death worldwide. To date, surgical repair or endovascular repair (EVAR) is the only effective treatment for aortic aneurysm, as no pharmacological treatment has been found effective. Aortic aneurysm, a focal dilation of the aorta, can be formed in the thoracic (TAA) or the abdominal (AAA) region; however, our understanding as to what determines the site of aneurysm formation remains q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
152
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(156 citation statements)
references
References 190 publications
(224 reference statements)
4
152
0
Order By: Relevance
“…In stark contrast to the effect in ECs, SMCs in alk5 mutants exhibit reduced proliferation and therefore reduced coverage of the OFT, explaining the lost integrity of the wall. This reduced SMC coverage is in agreement with the vascular defects reported in mice lacking Alk5 signaling globally, as well as in patients affected by aortic aneurysms (Larsson et al, 2001; Jana et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…In stark contrast to the effect in ECs, SMCs in alk5 mutants exhibit reduced proliferation and therefore reduced coverage of the OFT, explaining the lost integrity of the wall. This reduced SMC coverage is in agreement with the vascular defects reported in mice lacking Alk5 signaling globally, as well as in patients affected by aortic aneurysms (Larsson et al, 2001; Jana et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, many of the phenotypes we observed are similar to defects associated with aortopathies in clinical settings, pathologies often derived from mutations in TGF-β pathway genes (Loeys et al, 2006;Matyas et al, 2006;Camerota et al, 2019). At the morphological level, we observed that alk5a mutants present a thinning of the OFT outer wall, similar to patients affected by aortic aneurysms prone to dissection (Van Puyvelde et al, 2016;Jana et al, 2019). It is also interesting to note that the volume of the OFT wall decreased according to the age and size of the fish, similar to the decrease in aortic wall thickness in older patients (Fhayli et al, 2019;Clift et al, 2020).…”
Section: Clinical Perspective Of the Alk5a Cardiac Phenotypesupporting
confidence: 64%
“…Aortic aneurysm results from a series of adverse structural and cellular events, such as degradation of the ECM (extracellular matrix), loss or dysfunction of the endothelial cells (ECs) 1 and smooth muscle cells (SMCs). 2 , 3 Abdominal aortic aneurysm (AAA) is more prevalent in old men (≈1%–2% of 65 year olds) than in women (≈0.5% of 70 year olds). 4 6 Although linked to atherosclerosis, AAA can also occur in the absence of and independent from atherosclerosis and metabolic complications.…”
mentioning
confidence: 99%